Reproduksi Bahasa Krama Inggil melalui Kursus Pambiwara di Keraton Surakarta: (Studi Kasus tentang Strategi Keraton Surakarta dalam Upaya Mempertahankan Legitimasi Kekuasaan atas Kebudayaan Jawa) - Wilujeng, Panggio Restu; Samuel, Johanes Patricius Hanneman (Society, 2018)
This study aims to investigate Krama  Inggil language reproduction through courses of pambiwara keraton surakarta, as an effort by keraton to maintain power legitimacy on javanese culture, in relation to keraton's function that has been shifted into culture functionary. It is a qualitative study, a case study specifically. The theory used in this study is a theory by Pierre Bourdieu, which explains language as a symbolic power related to agent's survival strategy in the arena by utilizing possessed capital. This study shows that keraton has established a course of pambiwara as a strategy to reproduce cultural symbols that it has, particularly the use of Krama  Inggil language to maintain keraton's power legitimacy on javanese culture as the oldest heritage of Mataram monarchy.